Curricula as narratives and queer studies: emergences that question education (Praxis Educativa, 2024)
This article presents as an opportunity to think and problematize the relationships that are established in the knowledge networks that affect the school practice and the discourses that take place in the (dis)learning exercises that mark the teaching and student performativities and tension the curricular canons that seek themselves as a prescription. Therefore, eager for dialogues with Poststructuralist Studies, with them we seek to use curricular landscapes as events in classrooms, taking them as common experiences, which allow us to act and (dis) weave some discourses-shape-curricula that seek to ingraft normative practices to the performatized bodies. In this exercise, inspired by Queer Studies, life becomes unsubmissive, monstrous and provocative of a breaking in curricular codifications.
Keywords: Resumes; Queer Studies; Genre; Sexuality.